Application of DeLone and McLean Methods to Determine Supporting Factors for the Successful Implementation of Electronic Medical Records at Bali Mandara Eye Hospital - Dharma, I Gusti Ngurah Aditya; Sukadarmika, Gede; Pramaita, Nyoman (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Information technology in the health sector is currently an important factor in providing health services, especially hospitals. Bali Mandara Eye Hospital has implemented information technology in the registration process and bill issuance from 2015. Electronic Medical Record is a new application that will be implemented in 2021 at Bali Mandara Eye Hospital. Electronic Medical Record is a computerized system for recording patient health history. The implementation of electronic medical records at the Bali Mandara Eye Hospital for 1 year has many problems both in terms of regulations, systems and users. Therefore, the DeLone and McLean methods are used to determine the success rate of the implementation of electronic medical records. In this method, research is conducted on 6 variables, namely System Quality, Information Quality, Service Quality, Intention of Use, User Satisfaction and Net Benefits. From each variable, the researcher combines indicators from other researchers that are more appropriate for measuring electronic medical records. The results obtained that all statements submitted are valid. The success rate of electronic medical records at the Bali Mandara Eye Hospital was obtained at 3.22 or 80.50%. To be able to increase this value, it is recommended to improve the Information Quality, System Quality and User Satisfaction